2016
DOI: 10.1159/000454718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <b><i>Aloe</i></b> Sterol Supplementation on Skin Elasticity, Hydration, and Collagen Score: A 12-Week Double-Blind, Randomized, Controlled Trial

Abstract: Background/Aims: Our previous study confirmed that Aloe sterol stimulates collagen and hyaluronic acid production in human dermal fibroblasts. This study aims to investigate whether Aloe sterol intake affects skin conditions. Methods: We performed a 12-week, randomized, double-blind, placebo-controlled study to evaluate the effects of oral Aloe sterol supplementation on skin elasticity, hydration, and the collagen score in 64 healthy women (age range 30-59 years; average 44.3 years) who were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 736 publications
(40 citation statements)
references
References 66 publications
1
39
0
Order By: Relevance
“…Our recent clinical study suggested that the Aloe sterol intake induced a significant increase in the skin hydration of Japanese women’s skin that was protected from sunlight by clothing 15. In a basic research report, we suggested that the Aloe sterols prevented significant UVB irradiation-induced decreases in skin hydration, elasticity, and hyaluronic acid synthase 2 (Has2) in hairless mice 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent clinical study suggested that the Aloe sterol intake induced a significant increase in the skin hydration of Japanese women’s skin that was protected from sunlight by clothing 15. In a basic research report, we suggested that the Aloe sterols prevented significant UVB irradiation-induced decreases in skin hydration, elasticity, and hyaluronic acid synthase 2 (Has2) in hairless mice 14.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that the levels of skin moisture, skin elasticity, and collagen scores in the Aloe sterol group were higher than those of the placebo groups 15. Furthermore, ultrasound echogenicity revealed that Aloe sterol intake increased the amount of collagen in the dermis.…”
Section: Introductionmentioning
confidence: 91%
“…Aloe gel supplementation improves collagen production and reduces collagen‐degrading MMP‐1 gene expression, enhancing wrinkles and elasticity in photoaged human skin, with no dose‐response relationship (Cho et al, ). Aloe sterol ingestion contributes to collagen and HA production in human dermal fibroblasts ameliorating skin moisture, trans‐epidermal water loss and, skin elasticity (Tanaka et al, ).…”
Section: Key Market Segments Of Nutricosmetics Covered By Typementioning
confidence: 99%
“…Barley and soy seeds [Colour figure can be viewed at wileyonlinelibrary.com] Secondary metabolites FIGURE 7 Horsetail (Equisetum arvense L.) [Colour figure can be viewed at wileyonlinelibrary.com] 5.7.3 | Aloe vera (Figure 8)Aloe gel supplementation improves collagen production and reduces collagen-degrading MMP-1 gene expression, enhancing wrinkles and elasticity in photoaged human skin, with no dose-response relationship(Cho et al, 2009). Aloe sterol ingestion contributes to collagen and HA production in human dermal fibroblasts ameliorating skin moisture, trans-epidermal water loss and, skin elasticity(Tanaka et al, 2016).5.7.4 | Pine bark (Pinus pinaster; Figure 9)Pine bark extract supplements contain mainly flavonoids (catechins and procyanidins) and phenolic acids (caffeic, ferulic, and p-hydroxybenzoic acids) and are able to have photoprotective effect and to increase the hydration and the elasticity of the skin. Their biological effects are related to the increase of HA synthase, to the RNA expression, and to gene expression involved in collagen de novo synthesis (Pérez-Sánchez,Barrajón-Catalán, Herranz-López, & Micol, 2018).…”
mentioning
confidence: 99%
“…Furthermore, the same research group evaluated the effects of oral aloe sterol supplementation on skin elasticity, hydration, and the collagen score in 64 healthy Japanese women aged 30-59 years. It was concluded that continued aloe sterol ingestion contributes to maintain healthy skin and prevents the skin photo-aging [47] . Saito et al [48] investigated the effects of oral aloe vera gel powder (AVGP) containing aloe sterols on skin elasticity and the extracellular matrix in UVB-irradiated hairless mice.…”
Section: Effects Of Aloe Supplementation On Skin Photo-agingmentioning
confidence: 99%